Caudal-dependent cell positioning directs morphogenesis of the C. elegans ventral epidermis - Gilbert, S; Mullan, T; Poole, R; Woollard, A (Elsevier, 2020)
Strikingly, epithelial morphogenesis remains incomplete at the end of C. elegans embryonic development; newly hatched larvae undergo extensive remodelling of their ventral epidermis during the first larval stage (L1), when newly-born epidermal cells move ventrally to complete the epidermal syncytium. Prior to this remodelling, undivided lateral seam cells produce anterior adherens junction processes that are inherited by the anterior daughter cells following an asymmetric division during L1. These adherens junction processes provide the ventral migratory route for these anterior daughters. Here, we show that these processes are perturbed in pal-1/caudal mutant animals, resulting in their inheritance by posterior, seam-fated daughters. This causes aberrant migration of seam daughter cells, disrupting the ventral epidermis. Using 4D-lineaging, we demonstrate that this larval epidermal morphogenesis defect in pal-1 mutants can be traced directly back to an initial cell positioning defect in the embryo. pal-1 expression, driven by a single intronic enhancer, is required to correctly position the seam cells in embryos such that the appropriate cell junctions support the correct migratory paths of seam daughters later in development, irrespective of their fate. Thus, during ventral epithelial remodelling in C. elegans, we show that the position of migrating cells, specified by pal-1/caudal, appears to be more important than their fate in driving morphogenesis.